Brood care, pair bonds and plumage in southern African Anatini - Siegfried, W Roy (Wildfowl, 1974)
The incidence of males accompanying females with broods is compared in six Anas species: African Black Duck A. sparsa, Cape Teal A. capensis, African Yellowbill A. undulata, Red-billed Teal A. erythrorhyncha, Hottentot Teal A. punctata and Cape Shoveler A. smithii. Males accompany females with broods in those species which have extended pair-bonds. Length of pair-bond is influenced by ecological factors which shape a species’ social behaviour as well as features of its morphology. It is suggested that plumage brightness in males evolved as a result of sexual selection. In migratory forms the ecological conditions, regulating time and energy budgets, afford a relatively short period for elaborate, intense social courtship. Regular migrants have sexually dimorphic plumage. Most residents and nomads are monomorphic; this is attributed to heavier predation pressure and a lower but more evenly sustained productivity of food, permitting a relatively extended period for less intense, less elaborate social courtship.